Answer:
For f(x) = 2x + 3 and g(x) = -x 2 + 1, find the composite function defined by (f o g)(x)
(f o g)(x) = f(g(x))
= 2 (g(x)) + 3
= 2( -x 2 + 1 ) + 3
= - 2 x 2 + 5 Given f(2) = 3, g(3) = 2, f(3) = 4 and g(2) = 5, evaluate (f o g)(3)
Step-by-step explanation:
Answer:
g(1) = 0
There is a remainder of 10 so you can automatically cross out 3 and 4.
The correct answer is Undefined
I just did this in pre-calculus and I’m positive it is correct
The function has three real zeros. The graph of the function intersects the x-axis at exactly three locations.
Answer: Each fraction is greater than the previous fraction.
Step-by-step explanation:
The fractions given are:
2/3, 4/6, 8/12, 16/24
Note that
2/3 = 4/6 = 8/12 = 16/32
The Fractions are all equal. Each fraction is equivalent to 2/3
The pattern used here is:
2/3 × 2/2 = 4/6
4/6 × 2/2 = 8/12
8/12 × 2/2 = 16/24
16/24 × 2/2 = 32/48
Each fraction is equal to the previous fraction in the pattern multiplied by 2/2
Also, the next fraction in the pattern is 32/48.
The statement that "Each fraction is greater than the previous fraction" is incorrect. The fractions are all equal.